Single‐crystal neutron and X‐ray diffraction study of garnet‐type solid‐state electrolyte Li6La3ZrTaO12: an in situ temperature‐dependence investigation (2.5 ≤ T ≤ 873 K). Issue 1 (9th February 2021) - Redhammer, Günther J.; Meven, Martin; Ganschow, Steffen; Tippelt, Gerold; Rettenwander, Daniel
Abstract : Single‐crystal neutron and X‐ray diffraction methods were used to evaluate the exact crystal structure, Li site occupation and diffusion path of nominal Li6 La3 ZrTaO12 at six temperatures between 2.5 K and 873 K. Abstract : Large single crystals of garnet‐type Li6 La3 ZrTaO12 (LLZTO) were grown by the Czochralski method and analysed using neutron diffraction between 2.5 and 873 K in order to fully characterize the Li atom distribution, and possible Li ion mobility in this class of potential candidates for solid‐state electrolyte battery material. LLZTO retains its cubic symmetry (space group Ia 3 d ) over the complete temperature range. When compared to other sites, the octahedral sites behave as the most rigid unit and show the smallest increase in atomic displacement parameters and bond length. The La and Li sites show similar thermal expansion in their bond lengths with temperature, and the anisotropic and equivalent atomic displacement parameters exhibit a distinctly larger increase at temperatures above 400 K. Detailed inspection of nuclear densities at the Li1 site reveal a small but significant displacement from the 24 d position to the typical 96 h position, which cannot, however, be resolved from the single‐crystal X‐ray diffraction data. The site occupation of Li I ions on Li1 and Li2 sites remains constant, so there is no change in site occupation with temperature.